PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL SEKRETARIAT DAERAH KABUPATEN KARAWANG - Cahyanti Nurvitasari cahyanti; Solehudin; Banuara Nadeak (Jurnal Sosial Humaniora, 2022)
This study aims to examine and analyze the influence of work discipline and motivation on the performance of civil servants in SETDA Karawang Regency. The research was conducted using descriptive and verification methods, namely: collecting, presenting, analyzing and testing hypotheses and making conclusions and suggestions. Samples were collected using a non-probability sampling technique with purposive sampling as many as 144 people. The analytical technique used is the technique of scale range analysis and path analysis with the help of the Method of Succesive Interval (MSI), The correlation coefficient between the variables of Work Discipline and Motivation obtained a value of 0.469 which means it has a fairly strong, positive and significant correlation level between Work Discipline and Motivation. The partial effect of work discipline on employee performance is 0.433, which is greater than motivation, which is 0.109. So it can be stated that work discipline contributes more to employee performance than motivation. The simultaneous effect of work discipline and motivation on employee performance is 54.2% while the remaining 45.8% is another variable that was not examined.